Penyuluhan Pencegahan Penyakit Menular Melalui Edukasi Perilaku Hidup Bersih Di Lingkungan Padat Penduduk - Sitti Johri Nasela; Yona Sahalessy; Zulfikar Peluw; Masrikat Maya Diana Claartje; Zuriani Rizki (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Densely populated areas are at high risk for the spread of infectious diseases, such as diarrhea, acute respiratory infections (ARI), tuberculosis, and other environmentally related diseases. Low levels of community knowledge regarding Clean and Healthy Living Behaviors (PHBS), coupled with limited sanitation facilities, contribute to the high incidence of infectious diseases in these areas. This Community Service activity aims to increase community knowledge through intensive outreach on infectious disease prevention and PHBS implementation. The activity was conducted among 85 residents of RW 05, Kelurahan X, and included 85 participants. The methods used included outreach, handwashing demonstrations, leaflet distribution, and training on making homemade disinfectants. Evaluation used pre- and post-tests to determine improvements in community understanding. Results showed an average increase in knowledge from 56.7 to 87.4 after the activity. Ninety-three percent of participants considered the activity beneficial, and 78% stated they were ready to implement PHBS routinely. This activity has proven effective in increasing community understanding and skills in preventing infectious diseases. Continued mentoring is needed to ensure sustainable behavior change.